Efficacy Of Combination Fungicides Against Rice Sheath Blight And Glume Discoloration Diseases In Below Sea Level Wet Land Ecosystem (Journal of Plant Disease Sciences, 2020)
Field experiments were conducted at Rice Research Station, Moncompu, Alappuzha, Kerala for four consecutive seasons of Kharif 2017, Rabi 2017-18, Rabi 2018-19 and Kharif 2019 with the objective of evaluation of efficiency of newer and commercially available fungicides against rice sheath blight and glume discoloration diseases.The tested fungicides wereFlusilazole 12.5% + Carbendazim 25% SC, Azoxystrobin 18.2% W/W + Difenoconazole 11.4% W/W, Azoxystrobin 11%+Tebuconazole 18.3%W/W, Tricyclazole 18%+Mancozeb 62%WP, Zineb 68%+ Hexaconazole 4%WP, Mancozeb 50% + Carbendazim 25%WS, Fluxapyroxad 625g/L+Epoxiconazole 62.5G/L EC and Trifloxystrobin 25%+Tebuconazole 50% WG.Amongeight fungicides tested, Tricyclazole 18 % + Mancozeb 62% WP@2.5ml /lwas found most promisingcombination molecule against sheath blight and glume discoloration incidence followed by Zineb 68% + Hexaconazole 4% WP@ 2.5 g /l, Flusilazole 12.5 % + Carbendazim 25% SC @1ml /land Azoxystrobin 18.2% + Difenoconazole 11.4%w/w SC@1.0ml/l. The maximum yield was obtained from Flusilazole 12.5 % + Carbendazim 25% SC(5874 kg/ha) and Tricyclazole 18 % + Mancozeb 62% WP (5795 kg/ha) followed by Mancozeb 50 %+ Carbendazim 25%WS (5675 kg/a) and Zineb 68% + Hexaconazole 4% WP (5668 kg/ha). The control plot recorded with lowest yield of 3688 kg/ha.
Keywords: Rice; Sheath blight; glume discoloration; combination fungicide